2017
DOI: 10.1002/14651858.cd011109.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Probing for congenital nasolacrimal duct obstruction

Abstract: Background Congenital nasolacrimal duct obstruction (NLDO) is a common condition causing excessive tearing in the first year of life. Infants present with excessive tearing or mucoid discharge from the eyes due to blockage of the nasolacrimal duct system, which can result in maceration of the skin of the eyelids and local infections, such as conjunctivitis, that may require antibiotics. The incidence of nasolacrimal duct obstruction in early childhood ranges from 5% to 20% and often resolves without surgery. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Probing of the nasolacrimal system is traditionally the most commonly adopted surgical procedure in the management of CLNDO [39,40,41,42]. This procedure, which requires passing a probe down to the distal portion of the nasolacrimal system in order to break the obstruction, may be performed either in office with only the administration of local anesthetics or in the operating room in a surgical facility with general anesthesia [9]. In recent years, two different philosophies have been debating about the optimal timing of intervention; the first one suggests an early primary probing (6–9 months) because even if it is technically more challenging to manage an awake and often crying child, it would allow for avoiding the risks of general anesthesia and, according to some authors, the potential development of fibrosis due to the prolonged chronic inflammation of the NLD [20,23,43].…”
Section: Primary Probingmentioning
confidence: 99%
See 3 more Smart Citations
“…Probing of the nasolacrimal system is traditionally the most commonly adopted surgical procedure in the management of CLNDO [39,40,41,42]. This procedure, which requires passing a probe down to the distal portion of the nasolacrimal system in order to break the obstruction, may be performed either in office with only the administration of local anesthetics or in the operating room in a surgical facility with general anesthesia [9]. In recent years, two different philosophies have been debating about the optimal timing of intervention; the first one suggests an early primary probing (6–9 months) because even if it is technically more challenging to manage an awake and often crying child, it would allow for avoiding the risks of general anesthesia and, according to some authors, the potential development of fibrosis due to the prolonged chronic inflammation of the NLD [20,23,43].…”
Section: Primary Probingmentioning
confidence: 99%
“…In this regard, the authors found that early probing reduced overall symptoms of 3 months and was slightly more cost-effective in comparison with the deferred procedure; however, the possibility of resolving CLNDO in two thirds of the patients with only simple observation should be carefully taken into consideration [29]. In fact, probing is an invasive and blind procedure, which is not free from complications such as bleeding, damage of the nasolacrimal system and of the adjacent structures and inflammation with subsequent NLD fibrosis [9]. Young et al reported bleeding from the lacrimal punctum during the procedure in 20% of patients caused by the formation of a false passage [22].…”
Section: Primary Probingmentioning
confidence: 99%
See 2 more Smart Citations
“…If conservative therapy is ineffective, lacrimal duct probing would be advocated. Though controversy exists for the best timing for lacrimal probing [ 3 , 4 ], conservative treatment in the first year of life was generally recommended due the high spontaneous recovery rate of CNLDO [ 2 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%